Rancang Bangun Sistem Informasi Penjualan Sepatu Menggunakan Bahasa Pemograman PHP Dan MySQL Pada Aman Store Rantau Prapat - Nia Edi Putri; Syaiful Zuhri Harahap; Irmayanti Irmayanti; Angga Putra Juledi (Universitas Labuhanbatu, 2026)
The rapid development of information technology has pushed various business sectors, including Aman Store Rantau Prapat, to adapt digital technology to enhance operational efficiency and market reach. Currently, Aman Store still relies on a manual system, which results in inefficiencies in monitoring transactions and stock, as well as a limited market reach. This research aims to design and build a web-based shoe sales information system using PHP and a MySQL database. The system development follows the Waterfall method, which includes stages of requirement analysis, system design, implementation, testing, and maintenance. System modeling is represented using the Unified Modeling Language (UML), including Use Case, Activity, and Sequence Diagrams, to visualize actor-system interactions and business processes. The result of this research is a web-based application that provides digital product catalogs, online ordering and payment features, and automated stock management. Implementation of this system is expected to accelerate the transaction process, reduce human error, and expand market coverage beyond the local area, thereby increasing the store's competitiveness.